Maintaining bipartite matchings in the presence of failures - Sha, E.H.-M.; Steiglitz, K. (Parallel Processing Symposium, 7th International (IPPS '93, 1993)
The authors present an on-line distributed reconfiguration algorithm for finding a new maximum matching incrementally after some nodes have failed. Their algorithm is deadlock free, and with k failures maintains at least M-k matching pairs during the reconfiguration process, where M is the size of the original maximum matching. The algorithm tolerates failures that occur during reconfiguration. The worst-case reconfiguration time is O(k min( mod A mod , mod B mod )) after k failures, where A and B are the node sets, but simulations show that the average-case reconfiguration time is much better. The algorithm is also simple enough to be implemented in hardware.< >